Enhancement of Ovarian Tumor Detection by DR6-Targeted Ultrasound Imaging Agents in Laying Hen Model of Spontaneous Ovarian Cancer. Issue 8 (October 2016) - Barua, Animesh; Edassery, Seby L.; McNeal, Sa'Rah; Bahr, Janice M.; Bitterman, Pincas; Basu, Sanjib; Sharma, Sameer; Abramowicz, Jacques S.
Abstract : Objective: The lack of an effective early detection test leads to high case to death ratio of women with ovarian cancer (OVCA). To improve early detection, tumor-associated imaging targets need to be established and imaging agents to image these targets need to be developed. Targeted imaging agents offer potential for improvement of signal intensities from their targets. Expression of death receptor 6 (DR6) by ovarian malignant cells and tumor-associated microvessels increases during OVCA development and represents a novel target for ultrasound imaging. The goal of this study was to examine the feasibility of newly developed DR6-targeted ultrasound imaging agents in enhancing early detection of ovarian tumors in laying hen model of spontaneous OVCA. Materials and Methods: The study was conducted in an exploratory cross-sectional design using 4-year-old laying hens (n = 130). DR6-targeted imaging agents were developed by conjugating microbubbles with rabbit anti-chicken DR6 antibodies. Changes in signal intensity of ultrasound imaging were determined before and after injection of targeted imaging agents in hens with or without spontaneous OVCA. Following targeted imaging, normal or tumor ovaries were processed for histopathological and immunohistochemical studies. Results: DR6-targeted imaging agents bound with their targets expressed by malignant cells and tumor-associated microvessels in the ovary. Compared with pretargeted imaging, targeted imaging is enhanced by approximately 40% ultrasound echo signal intensity ( P < 0.001) from early- and late-stage OVCA. Differences in signal enhancement were not observed among different histological subtypes of OVCA at early or late stages. Higher imaging signal intensities were associated with enhancement in DR6 expression by ovarian malignant cells and increase in the frequency of DR6-expressing microvessels during OVCA development. Conclusions: The results of this study suggest that DR6-targeted imaging agents enhance the visualization of ovarian tumors and tumor-associated microvessels in hens with early-stage OVCA and will form a foundation for clinical studies.